Water Supply and Sanitation in Kenya : Turning Finance into Services for 2015 and Beyond - World Bank (World Bank, Nairobi, 2013)
The architecture of the water supply and sanitation subsectors in Kenya has undergone significant change in the last decade, in response to a slow deterioration of urban services through the 1980s and '90s. Initiated with a new water act in 2002, significant policy revision and restructuring of institutional roles is still ongoing and will need to be aligned with the new Constitution of Kenya 2010. Most of the reform emphasis has been in the water supply subsectors, especially urban, but sanitation is now regaining emphasis with a new policy published in 2007 and a strategy and investment plan in development. These reforms of the enabling environment are beginning to yield impacts in the coverage and quality of services. Kenya's challenge is to finalize the reform of enabling aspects such as strategies and investment plans, further clarifying roles and responsibilities, at the same time as significantly scaling up resources and systems for implementing the development of new services on the ground. Finally, in terms of checks and balances, while the monitoring and evaluation architecture is elaborate, greater use of the findings captured by information systems and reports is needed to drive performance improvements. The African Ministers Council on Water (AMCOW) Second Country Status Overview (CSO2) has been produced in collaboration with the Government of Kenya and other stakeholders.